Vector competence of Aedes aegypti from New Caledonia for the four recent circulating dengue virus serotypes. - Olivia O'Connor; Elodie Calvez; Catherine Inizan; Nicolas Pocquet; Vincent Richard; Myrielle Dupont-Rouzeyrol (Public Library of Science (PLoS), 2020)
In New Caledonia (NC), Aedes aegypti is the only proven vector of dengue virus (DENV), which is the most prevalent arbovirosis in NC. Since World War II, the four DENV serotypes have circulated regularly in NC. The epidemiological profile, however, has evolved over the last ten years, with the persistence of DENV-1 circulation and the co-circulation of several DENV serotypes. The current study evaluated the ability of Ae. aegypti from NC to transmit four DENV serotypes (and two DENV-1 genotypes) isolated during recent outbreaks in NC. An Ae. aegypti F1 generation was twice independently orally challenged with each DENV strain (107 FFU/ml). Infection, dissemination and transmission rates and transmission efficiency were measured at day 7 and 14 post-exposure, as well as the quantity of infectious virus particles. Mosquito infection was observed as early as 7 days post-infection. Infection rates between 18 and 58% were measured for all DENV serotypes/genotypes tested. Although dissemination rates ranged from 78 to 100%, transmission efficiencies were low, with values not exceeding 21% at 14 days post-infection for all DENV strains. This study shows that NC Ae. aegypti are moderately competent for DENV in laboratory conditions. In link with epidemiological data, these results suggest implication of other factors in the sustained circulation of DENV-1 in New Caledonia.